Steroid induced ocular complications in idiopathic nephrotic syndrome: a cross sectional single center study - Zulfiqar, Zunaira; Fatema Lanewala,; Sabeeta Khatri,; Irshad Bajeer,; Madiha Aziz,; Seema Hashmi, (Journal of the Pakistan Medical Association, 2024)
Objective: To screen children receiving steroids to identify ocular complications and their prevalence. Method: The cross-sectional study was conducted at the Paediatric Nephrology and Ophthalmology departments of the Sindh Institute of Urology and Transplantation, Karachi, from May to October 2022, and comprised patients who received at least 1500mg cumulative steroid dose for a minimum of 3 months. They were screened for steroid-sensitive or steroid-resistant nephrotic syndrome. Ocular examinations, including visual acuity, intraocular pressure, slit-lamp biomicroscopy, lens examination and fundus evaluation, were performed. Data was analysed using SPSS 22. Results: Of the 124 subjects with mean age 8.15±2.03 years (range: 6-12 years), 64(51.6%) were boys. Steroid-sensitive nephrotic syndrome was present in 97(78%) cases. The mean cumulative steroid dose was 3999.31±1564.22mg. Overall, 36(29%) children developed ocular complications. Blood pressure, number of relapses and the duration of treatment were significantly associated (p<0.05). Conclusion: Refractive errors were the most frequent side effects/complication seen among children with nephrotic syndrome who received prolonged corticosteroids. Key Words: Nephrotic syndrome, Corticosteroids, Cataract, Glaucoma, Refractive error.